1, 3:2, 4-Dibenzylidene-d-sorbitol (DBS) and its derivatives – efficient, versatile and industrially-relevant low-molecular-weight gelators with over 100 years of history and a bright future. Issue 24 (28th June 2015) - Okesola, Babatunde O.; Vieira, Vânia M. P.; Cornwell, Daniel J.; Whitelaw, Nicole K.; Smith, David K.
<x xml:space="preserve">Abstract</x> DBS is an efficient, versatile, low-molecular-weight gelator with a wide-range of industrial applications – greater understanding of its self-assembly and the creation of new derivatives are expanding the scope of this fascinating family of gels.